One-time fertilization in flue-cured tobacco: nutrient dynamics, chemical composition and economic performance across different soil textures - Zhu, Zhen; Peng, Jianwei; Zhao, Ajuan; Wu, Boran; Ding, Chunxia; Li, Bo; Han, Yongliang (Frontiers in Plant Science, 2025)
IntroductionOne-time fertilization is a promising strategy to reduce labor costs and improve efficiency in agriculture. While its benefits are documented in staple crops (e.g., wheat, rice, maize), the efficacy of this approach in high-value crops like flue-cured tobacco and its interaction with soil texture remain poorly understood. Therefore, this study aimed to 1) evaluate the feasibility of one-time basal application of a specialized fertilizer in flue-cured tobacco, and 2) determine how soil texture (loamy vs. sandy) mediates its agronomic and economic efficacy.MethodsFour treatments were compared: a no-fertilizer control (CK), conventional split fertilization (CF), one-time application of specialized fertilizer (T1), and specialized fertilizer plus a seedling-raising fertilizer (T2).ResultsResults showed that in loamy soil, T1 and T2 significantly enhanced late-stage nitrogen (N) and potassium (K) accumulation, increasing N use efficiency by 54.5~56.7% compared to CF. The economic gains were highly soil-specific. Although both T1 and T2 reduced labor costs, T2 in sandy soil generated the highest net income. It significantly increased production value by 14.8% and the proportion of high-grade tobacco by 16.7%, respectively (p<0.05), compared to CF. This gain was driven by improved leaf quality rather than increased biomass yield.DiscussionLoamy soil excelled in nutrient retention and utilization efficiency. This study demonstrates that soil texture mediates the success of one-time fertilization. The T2 strategy offers a profitable, labor-saving alternative, especially in sandy soils, providing a scientific basis for soil-specific fertilization policies to optimize productivity and economic sustainability.